Two populations of gamma-ray burst radio afterglows - Hancock, Paul; Gaensler, B.; Murphy, T. (IOP Publishing Ltd., 2013)
The detection rate of gamma-ray burst (GRB) afterglows is ~30% at radio wavelengths, much lower than in the X-ray (~95%) or optical (~70%) bands. The cause of this low radio detection rate has previously been attributed to limited observing sensitivity. We use visibility stacking to test this idea, and conclude that the low detection rate is instead due to two intrinsically different populations of GRBs: radio-bright and radio-faint. We calculate that nomore than 70% of GRB afterglows are truly radio-bright, leaving a significant population of GRBs that lack a radio afterglow. These radio-bright GRBs have higher gamma-ray fluence, isotropic energies, X-ray fluxes, and optical fluxes than the radio-faint GRBs, thus confirming the existence of two physically distinct populations. We suggest that the gamma-ray efficiency of the prompt emission is responsible for the difference between the two populations. We also discuss the implications for future radio and optical surveys.